G499(P) Clinical diagnostic evaluation of a point of care pcr-based rsv test – a prospective, observational multi-centre cohort study. (May 2019) - Allen, AJ; Gonzalez-Ciscar, A; Lendrem, C; Simpson, AJ; Kumar, P; Eastham, K; Brodlie, M
Abstract : Aims: To prospectively evaluate the diagnostic accuracy of the cobas Liat ® point of care system for respiratory syncytial virus (RSV) in children under 2 years of age presenting with viral respiratory symptoms in a 'real-life' NHS setting. Methods: A prospective, observational cohort study was performed at a district general and a tertiary children's hospital between September 2017 and May 2018 (the 'DEC-RSV study'). Children under 2 years of age presenting with an acute respiratory illness where the attending clinician considered that RSV infection was in the differential diagnosis were recruited following informed consent. A nasopharyngeal aspirate sample was collected by standard procedure, split and analysed using the RSV component of the Roche cobas Liat ® Influenza A/B and RSV PCR point of care system in a ward setting and by the usual laboratory-based PCR testing procedure (Argene platform at the district general hospital and Luminex at the children's hospital). Discrepant laboratory samples were re-tested on the alternative laboratory-based system. Secondary outcomes included time to result. Results: A total of 186 participants were recruited (median age 4 months; 68% had an admission diagnosis of bronchiolitis) with 161 final data sets suitable for diagnostic accuracy analysis (25 data sets were not usable due to: 1 no sample, 8 missing laboratory-based results and 16 invalid cobas Liat ® results). Prior to discrepancy testing, sensitivity of the cobas Liat ® test for RSV detection was 98.9% (95% CI 96–99.7) with specificity of 94.3% (95% CI 89.8–96.9). After discrepancy testing this increased to sensitivity of 100% (95% CI 97.9–100) and specificity 98.5% (95% CI 95.5–99.5). Median time to result, including sample collection time, was 0.6 hours (IQR 0.5–1) for cobas Liat ® and for the standard laboratory-based testing procedure at the district general hospital 29.7 hours (IQR 27.9–49.0) and the children's hospital 27.9 hours (IQR 25.6–48) which involved batch testing at both sites. Conclusions: The cobas Liat ® point of care system has excellent sensitivity and specificity for the detection of RSV in nasopharyngeal aspirate samples from children under 2 years of age presenting with respiratory viral symptoms. Diagnostic accuracy is comparable with laboratory-based platforms with favourable time to result. #Presented on behalf of the DEC-RSV study team